2019
DOI: 10.29252/sjku.24.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect education based on trans-theoretical model on reduction of the prevalence of gingivitis among pregnant women: Application of Telegram social network

Abstract: Background and Aim: Gingivitis has high prevalence among pregnant women and educational programs have resulted in little success in the improvement of this disorder. The aim of this study was to determine the effect of trans-theoretical model based education on reduction of the prevalence of gingivitis among pregnant women through Telegram social network. Materials and Methods: This experimental study was conducted in Sanandaj City, in the west of Iran in 2018. 160 pregnant women were assigned to intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The findings of this study indicated that three months after the intervention, the perceived benefits of tooth brushing behavior were enhanced in the intervention group in comparison with the control group. These findings are in agreement with those of the study by Anderson et al, 38 Shamsi et al, 23 Rahmani et al, 24 and Khani Jeihooni et al 9 Perceived benefits are perceptions of the positive outcomes of conducting a healthy behavior. In this case, individuals are likely to spend their resources and time on activities in which the possibility of positive outcomes is higher.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study indicated that three months after the intervention, the perceived benefits of tooth brushing behavior were enhanced in the intervention group in comparison with the control group. These findings are in agreement with those of the study by Anderson et al, 38 Shamsi et al, 23 Rahmani et al, 24 and Khani Jeihooni et al 9 Perceived benefits are perceptions of the positive outcomes of conducting a healthy behavior. In this case, individuals are likely to spend their resources and time on activities in which the possibility of positive outcomes is higher.…”
Section: Discussionsupporting
confidence: 90%
“… 17 In Iran, limited interventional studies have been conducted in this regard. 18 - 24 On the other hand, social networks have the potential to involve people in health interventions due to various aspects such as social support, empowerment, peer pressure, and interactive exchange of information and feelings. 25 Nonetheless, social networks have been used in limited oral health interventions during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadi Rizeh showed that compared to educational booklets, e-learning could increase the satisfaction and awareness of primiparous women to pregnancy care (Rahmani et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, social networks have become a place for education and have important implications for health. In these networks, people receive information from different sources and constantly change their behavior (21). Considering that many studies have shown that parents of children with cancer bear a high care burden (4,22).…”
Section: Introductionmentioning
confidence: 99%